Goodwill Indemnity in the Bed of Procrustes - Benito, Marco de; Menéndez, Santiago (Wolters Kluwer, 2024)
Despite their social and economic importance, commercial distribution contracts lack a specific legal framework in most European countries. This silence has led to a high level of litigation, often following the termination of the contract. Goodwill indemnity has been a point of contention due to the complexity of its nature and the uncertainty as to the methods to be used to quantify it. Taking Spain as an example of the common European problem, the authors examine whether there is a reasonable basis that justifies the granting of goodwill indemnity to distributors. More specifically, the authors analyze whether and under what conditions an analogous application of the Law on agency contracts, which derives from an EU Directive that has now been transposed in all EU countries, is legitimate and how it interacts with the relevant general principles of law, namely the prevention of unjustified enrichment and good faith. Based on the legal conclusions reached, the authors stress the need to use the most appropriate and accurate financial methodology to quantify the actual monetary value of the indemnity in each case, understood as an intangible financial asset, without imposing a ceiling.
Keywords: 56 Ciencias Jurídicas y Derecho::5605 Derecho y legislación nacionales::5605.02 Derecho civil; ODS 16 - Paz, justicia e instituciones sólidas